The Performance of Monetary Policy Amid the Spread of Virtual Currency Transactions - Abderrazak Zehouani, Zakaria Messaoudi, Abdeldjalil Houidi (Journal of Informatics Education and Research, 2024)
This research paper explores the conceptual framework of virtual currencies, detailing their definition, distinctions from other currencies, acquisition mechanisms, and key characteristics. The study examines the rise of virtual currencies as a new form of electronic payment, highlighting their differences from electronic money and traditional currencies. Focusing on Algeria, it discusses the legal stance on virtual currency transactions and their potential impact on monetary policy. Virtual currencies, such as Bitcoin, are decentralized and exist solely online, offering unique benefits and challenges. The results of this research emphasize the differences between virtual and electronic currencies, the various types of virtual currencies, and their advantages and disadvantages. As virtual currencies continue to gain global recognition, central banks will need to innovate new tools to adapt to this evolving financial technology. The paper concludes by suggesting that central banks should regulate virtual currencies through dedicated legal frameworks, especially in light of the disruptions caused by the COVID-19 pandemic.